Fisher Behaviour and its Implications for the Governability of the Inshore Fisheries in Atlantic Canada - Andrews, Evan (University of Waterloo, 2020)
The purpose of this dissertation is to advance a comprehensive understanding of fisher behaviour (i.e., current and former boat owners and crew who harvest multiple species) to strengthen the governability of the inshore fisheries in Atlantic Canada. Here, fisher behaviour is defined as individual fishers’ and groups of fishers’ actions that result from the mental processing and social negotiation of change and uncertainty in physical and social environments. Understanding how and why fishers behave in relation to changes in fish stocks and management decisions is key social scientific knowledge for strengthening governability. Yet, there has been limited progress on clarifying, defining, and explaining fisher behaviour in ways that reflect local contexts in the inshore fisheries in Atlantic Canada and coastal fisheries more broadly. This dissertation’s empirical research is guided by three overarching research objectives: (1) to critically examine fisher behaviour in peer-reviewed scientific literature for theoretical characterizations and empirical explanations; (2) to cultivate evidence-based insights about fisher behaviour and its motivations in relation to change and uncertainty in Newfoundland and Labrador; and (3) to identify strategies to strengthen the governability of Atlantic Canada’s inshore fisheries, including consideration of barriers and opportunities to incorporate fisher behaviour in science, policy, and management to advance multiple governance objectives. This dissertation used a mixed-method design that combined a systematic scoping review of fisher behaviour in coastal fisheries settings research with a case study research in Atlantic Canada. A systematic scoping review of peer-reviewed papers (n=104) was conducted to examine fisher behaviour’s characterizations, explanations, and implications for governance in the scientific literature (Chapter Two). Case study research included two aspects. First, an examination was conducted of inshore fisher behaviours in Newfoundland and Labrador by ...